Hypanartia splendida Rothschild, 1903 (Lepidoptera, Nymphalidae, Nymphalini) a rare species from the central rainforest of Peru - Grados, Juan (2014)
The species Hypanartia splendida Rothschild, 1903 was described from Perú, without giving further information about its type locality. After 105 years, the April 6 2008, a male specimen was collected at the upper parts of Yanachaga-Chemillén National Park, Pasco, Peru. This is the first specimen with precise collection data.